1999
DOI: 10.1115/1.2834136
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear of Aluminum-Silicon Carbide Metal Matrix Composites

Abstract: The sliding wear of an aluminum matrix composite, reinforced with different volume fraction of particles, against a stainless-steel slider has been studied. In dry conditions, i.e., unlubricated tests, the pairs (slider and specimen), wear. When rubbing against an aluminum alloy (unreinforced), the slider does not wear but the aluminum alloy wears quickly by adhesion. In dry conditions, both slider and composite wear, but there is a minimum wear rate for this pair at a critical volume fraction of reinforcing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In general, with increase in sliding distance and load, the wear rate increases in 7075 aluminium alloy [5]. The formation of tribo-layeror mechanically mixed layer has been described to reduce the wear rate [6] and affected by load level, sliding speed and reinforcement content [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, with increase in sliding distance and load, the wear rate increases in 7075 aluminium alloy [5]. The formation of tribo-layeror mechanically mixed layer has been described to reduce the wear rate [6] and affected by load level, sliding speed and reinforcement content [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for highly loaded composites are in line with previous research on the wear of composites containing low reinforcement content, which indicates that with increasing the reinforcement, wear resistance increases. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained for highly loaded composites are in line with previous research on the wear of composites containing low reinforcement content, which indicates that with increasing the reinforcement, wear resistance increases. 35,36 Wear mechanism. The wear mechanism changed from adhesive-abrasive base alloy to the soft-mild adhesive regime with increasing the Al 2 O 3 content.…”
Section: Wear Propertiesmentioning
confidence: 99%
“…It is clear that the reinforced particles colloid with the steel surface material leading to transfer of iron and produce a mechanical mixed layer. The mechanically mixed layer formed between the pin and the surface plays a vital role in reduction of wear in the composite samples [55][56][57][58][59][60][61][62]. The oxide and iron peaks present in sample S3 is more when compared with other samples and it has been concluded that wear resistance has increased.…”
Section: Evaluation Of Wear Rate and Coefficient Of Frictionmentioning
confidence: 99%